2010
DOI: 10.1134/s0021364010150014
|View full text |Cite
|
Sign up to set email alerts
|

On the collisions between particles in the vicinity of rotating black holes

Abstract: Scattering of particles in the gravitational field of rotating black holes is considered. It is shown that scattering energy of particles in the centre of mass system can obtain very large values not only for extremal black holes but also for nonextremal ones. Extraction of energy after the collision is investigated. It is shown that due to the Penrose process the energy of the particle escaping the hole at infinity can be large. Contradictions in the problem of getting high energetic particles escaping the bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
117
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 13 publications
11
117
0
4
Order By: Relevance
“…Thus although this scenario cannot be realized in a straightforward manner, this is possible due to multiple scattering. It is worth reminding that multiple scattering scenario is necessary ingredient in another context -for the BSW effect near nonextremal black holes [20]. Now, it can be used for extremal black holes and head-on collisions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Thus although this scenario cannot be realized in a straightforward manner, this is possible due to multiple scattering. It is worth reminding that multiple scattering scenario is necessary ingredient in another context -for the BSW effect near nonextremal black holes [20]. Now, it can be used for extremal black holes and head-on collisions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One is a back-reaction argument against the acceleration given by [4,5] but implicitly disputed by [7,8]. Another, for us the most urgent issue to be addressed, is that of the limiting energy at infinity and the amount of any escaping flux of energetic annihilation debris [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Originally, the BSW effect was discussed for maximally rotating black holes [1] that entailed some doubts with respect to attempts to relate it to realistic astrophysical context [9], [10]. Meanwhile, later on, it was shown that the scenario of multiple scattering leads to the possibility of the BSW effect in the Kerr background even for nonextremal black holes [11] that was extended to generic dirty black holes [8].…”
mentioning
confidence: 99%